Processing and characterisation of aramid/carbon hybrid fibre reinforced polypropylene composites / Muhammad Rafiq bin Mohd Isa - Mohd Isa, Muhammad Rafiq (2014)
Hybrid composites of aramid fibre/carbon fibre/polypropylene (PP) with three total fibre volume fraction (Vf) and five fibre proportions (100:0, 75:25, 50:50, 25:75 and 0:100 V:V %) were prepared by extrusion and injection moulding. The moulded composite specimens were characterised for thermal, dynamic mechanical and mechanical properties. The results from the analysis were supported by scanning electron microscope images. Thermogravimetric analysis (TGA) revealed that the hybridisation of fibres produces hybrid composites with better thermal properties compared to the single fibre composites. Differential scanning calorimetric (DSC) study showed that the incorporation of the fibres did not significantly alter the melting behaviour of the composites. The crystallinity of the matrix was found to be greatly affected by the total Vf. Dynamic mechanical analysis (DMA) showed an increase in the storage modulus (E’) indicating higher stiffness in the hybrid composites as compared to the aramid fibre composites. Carbon fibre content showed a strong influence on the magnitude of E’. The tensile properties of some hybrid composites exceed the properties of the single fibre composites. However, based on the SEM image of the fractured surface, it was found that the interfacial interaction between the matrix and fibres is weak. On the other hand, hybridisation reduced the flexural properties of the composites compared to its single fibre counterpart. Flexural properties were found to be more sensitive to total Vf, where composites with higher total Vf would have better flexural modulus. For all composites tested, the peak load (P) and critical stress intensity factor (Kc) increased with increasing carbon fibre contents. By contrast, the fracture energy (W) and critical strain energy release rate (Gc) were decreased with increasing carbon fibre content in hybrid composites. The hybrid composite showed superior impact properties when compared to its non-hybrid counterpart. In a nutshell, hybridisation of the fibres improved the impact properties of the composites.